The West-East Interreligious Discourse: Reading from Said Nursi’s Risale-i Nur - Hamsah, Ustadi (Journal of Al-Tamaddun, 2025)
This article takes a unique approach in exploring the foundational epistemological and philosophical structure underlying interreligious relations, a crucial aspect that has been largely unexplored in previous studies. This investigation is of utmost importance, as it forms the basis for understanding the increasingly polarized nature of interreligious relations between the Western and Eastern spheres. The study seeks to elucidate the fundamental epistemological framework that underpins the paradigmatic contestation in interreligious discourse. The research methodology entails a comprehensive philosophical analysis of Said Nursi’s seminal work, Risale-i Nur. The findings identify three pivotal factors driving this contestation: first, distinct thought structures rooted in specific regional contexts; second, a dichotomous interpretation of human relations; and third, a predominantly rational rather than ethical approach to understanding reality. The study concludes that ideologizing paradigms within interreligious discourse has engendered contentious relationships. This ideologization is subsequently challenged by ideological critique, leading to dialectical interactions. As a result, this paradigmatic dialectic perpetuates a cycle of superior-inferior dynamics in interreligious discourse.